A comparative content analysis of news articles on crimes against members of the LGBT in Balita and Pilipino Star Ngayon from January 2009 to June 2011 - Quinones, Diosa Angelica Elpidama (2012)
"This study is a comparative content analysis of two Philippine tabloids, namely Balita and Pilipino Star Ngayon, and how they report crimes against Lesbian, Gay, Bisexual, Transgender (LGBT) victims. The terms used to describe victims and suspects, types of crimes, and motives were considered as variables in this study. Interviews with reporters and editors from the said tabloids were gathered to complement the results of the data from the articles. The primary goal of this study is to compare how these two tabloids present LGBTs in crime stories. The secondary goal is to check if these tabloids followed or violated the seventh paragraph in the Journalist Code of Ethics, which states "I shall not in any manner ridicule, cast aspersions on or degrade any person of reason of sex, creed, religious belief, political conviction, cultural and ethnic origin". Another secondary goal is to get the reaction from the LGBT community on how these articles affect them. By studying news articles about LGBT victims in these tabloids, the researcher hopes to add empirical data to the current field of knowledge on LGBT and gender studies in the local setting."